Strategy of Rukun Tani Sumberejo Pakel to Fight for Land Rights in Agrarian Conflict in Banyuwangi Regency - Wisnujati, Ganis; Nurhandjati, Nurul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study analyzes the strategies of Rukun Tani Sumberejo Pakel in building movement resilience to defend land rights contested by PT Bumi Sari in Pakel Village, Banyuwangi Regency, during the period 2020–2025. The research adopts a qualitative approach and utilizes data collection methods including observation, interviews, and document analysis. The analytical process involved data reduction, data display, and conclusion drawing. The findings demonstrate that Rukun Tani adopted resistance strategies that were adaptive to the elvolving dynamics of the agrarian conflict. In terms of internal interaction, the social movement engaged in recruitment, capacity building, and organizational management. In its interaction with authorities, the movement organized land occupations and public demonstrations, while also pursuing legal and digital avenues of resistance. Furthermore, in its interaction with security forces, Rukun Tani combined confrontational actions, formal procedures, and social media campaigns. As a result, the movement was able to expand its strategic reach into institutional arenas. The study concludes that such strategies have played a significant role in enhancing the movement’s resilience and sustaining its long-term struggle.